Path-Goal Theory-based Leadership Development Deployment Guidelines for the Middle Managers of an International University in China - Chen, Liyan; Fernando, Maria Socorro C. L. (ABAC ODI JOURNAL Vision. Action. Outcome, 2022)
This research aims to 1) determine the current and desired situation of the middle managers’ leadership behavior and leadership performance based on path-goal theory, 2) identify the significant differences between current and desired middle managers’ leadership behavior, 3) explore ideas of key managers on leadership behavior and effectiveness through interviews, and 4) develop the final leadership effectiveness development deployment strategies based on the quantitative and qualitative findings. Questionnaire surveys and focus group discussions were used to collect data to identify and determine the significant difference between leadership behaviors and leadership effectiveness. The participants in this study were 67 teachers from Heilongjiang International University in China. Data analysis used frequency, percentage, paired-sample T-test for quantitative data, and Content analysis for qualitative data. Through quantitative research, it is found that focus should be given to Directive Leadership as priority, then Supportive Leadership and Participative Leadership, Achievement Leadership, and Leadership Effectiveness. The results of qualitative data analysis shows that there are four strategies for the development of leadership behaviors and leadership effectiveness.